(untitled) (Journal of Universal Science Research, 2023)
In this article you will be explained the necessity of proverbs. It is devoted to the significance of proverbs and sayings in people’s everyday life or communication. We know that proverbs are wise sayings that can give advice about real life. They are culturally specific, yet their meaning has the universality and everyone can relate to them in some way and on some level. There is a proverb for almost in any situation. There are some English proverbs and sayings and their equivalents with Uzbek language.